Pengaruh Penjualan Dan Biaya Operasional Terhadap Laba Bersih Pada Perusahaan Perkebunan Sawit yang Terdaftar Di Bursa Efek Indonesia 2020-2023 - Indra Bayu lesmana; Iqbal, Johandri; Saputra, Ferdyan Wana (Journal of Applied Accounting And Business, 2025)
This study is entitled "The Effect of Sales and Operating Costs on Net Profit in Palm Oil Plantation Companies Listed on the Indonesia Stock Exchange in 2020-2023". The purpose of this study is to analyze the simultaneous effect of sales and operating costs on the company's net profit. The methodology used in this study is secondary data analysis obtained from the annual reports of companies listed on the Indonesia Stock Exchange in the specified period. The independent variables in this study consist of sales and operating costs, while the dependent variable is net profit. The results of the study indicate that there is a significant effect between sales and operating costs on net profit, which indicates the importance of effective management in both aspects to improve the company's financial performance. This study contributes to the understanding of financial management in the palm oil plantation sector and can be used as a reference for stakeholders in making decisions related to business strategy.